Effect of Perineal Massage during Second Phase of Labor on Episiotomy and Laceration Rates among Nulliparous women - * M (MSc.); * C (MSc.); * N (MSc.); * T (MSc.); ** Y (B.Sc) (Tehran University of Medical Sciences, 2009)
Background & Aim: Routine episiotomy is often considered unnecessary. Episiotomy is associated with short- and long-term morbidities such as suturing, possible bleeding, infection, urinary and fecal incontinences, and dyspareunia. It has also adverse effects on self-esteem and mother-infant bonding. This study aimed to determine the effect of perineal massage during second stage of labor on perineal outcome among nulliparous women. Methods & Materials: This was a randomized controlled clinical trial. At 38-42 weeks of gestation, nulliparous women expecting normal vaginal delivery of a singleton were asked to join the study. Two hundred and four women were randomly allocated into the intervention and control groups. Participants signed the consent forms. In the intervention group, during the pushing time in the second phase of labor, the midwife inserted two fingers inside the vagina and used a sweeping motion gently to stretch the perineum. The control group received routine care. The rates of episiotomy and laceration were calculated. Results: In the intervention group, the rate of intact perineum, episiotomy, and laceration were 43.5%, 16.5%, and 40%, respectively and in the control group, they were 2.4%, 80% and 17.6%, respectively (P<0.001). In the intervention group, the first- and second-degree lacerations were 28.2% and 11.8%, respectively; but, the third and fourth degree lacerations were not seen. In the control group, first, second, and third degree lacerations were 4.7%, 7.1%, and 5.9%, respectively (P<0.001). The fourth degree laceration was not seen. The mean duration of the second stage of labor in the intervention and control groups were 40.06±20.74 and 51.06±21.23 minutes, respectively (P=0.003). The Mean of the first minute Apgar score was 8.51±0.76 and 8.73±0.60 in the intervention and control groups, respectively. The mean of the five minute Apgar score was 9.58±0.62 and 9.78±0.47, respectively (P=0.102). Conclusion: This study showed that perineal massage reduces the rate of episiotomy and the degree of lacerations in the second stage of labor. Massage may increase blood flow, elasticity, relaxation, and softness of the perineum.   Key words: perineum, massage, episiotomy, lacerations